PH‐Cleavable Nucleoside Lipids: A New Paradigm for Controlling the Stability of Lipid‐Based Delivery Systems. Issue 11 (18th September 2015) - Oumzil, Khalid; Benizri, Sébastien; Tonelli, Giovanni; Staedel, Cathy; Appavoo, Ananda; Chaffanet, Max; Navailles, Laurence; Barthélémy, Philippe
Abstract: Lipid‐based delivery systems are an established technology with considerable clinical acceptance and several applications in human. Herein, we report the design, synthesis and evaluation of novel orthoester nucleoside lipids (ONLs) for the modulation of liposome stability. The ONLs contain head groups with 3′‐orthoester nucleoside derivatives featuring positive or negative charges. The insertion of the orthoester function in the NL structures allows the formation of pH‐sensitive liposomes. ONL‐based liposomes can be hydrolyzed to provide nontoxic products, including nucleoside derivatives and hexadecanol. To allow the release to be tunable at different hydrolysis rates, the charge of the polar head structure is modulated, and the head group can be released at a biologically relevant pH. Crucially, when ONLs are mixed with natural phosphocholine lipids (PC), the resultant liposome evolves toward the formation of a hexadecanol/PC lamellar system. Biological evaluation shows that stable nucleic acid lipid particles (SNALPs) formulated with ONLs and siRNAs can effectively enter into tumor cells and release their nucleic acid payload in response to an intracellular acidic environment. This results in a much higher antitumor activity than conventional SNALPs. The ability to use pH‐cleavable nucleolipids to control the stability of lipid‐based delivery systems represents a promising approach for the intracellular delivery of drug cargos. Abstract : Orthoester nucleoside lipids (ONLs) reported here are the first examples of pH‐cleavable lipids that generate hexadecanol in the bilayers resulting in destabilization of vesicles under weak acidic conditions. Stable nucleic acid lipid particles (SNALPs) formulated with ONLs and siRNAs can effectively release their nucleic acid payload in response to an intracellular acidic environment. pH‐cleavable ONLs releasing fatty alcohols represent a promising approach for the intracellular delivery of drug cargos.